1987
DOI: 10.1115/1.3248028
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between Free-Stream Turbulence and Stagnation Region Heat Transfer

Abstract: A study has been conducted at the NASA Lewis Research Center to investigate the mechanism that causes free-stream turbulence to increase heat transfer in the stagnation region of turbine vanes and blades. The work was conducted in a wind tunnel at atmospheric conditions to facilitate measurements of turbulence and heat transfer. The model size was scaled up to simulate Reynolds numbers (based on leading edge diameter) that are to be expected on a turbine blade leading edge. Reynolds numbers from 13,000 to 177,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Also, at a fixed time, hot and cold spots alternate in the streaks. Such temperature variations are consistent with near-wall flow and surface visualizations reported in the literature [3][4][5]7] and have been attributed to variations in near-wall fluid temperature that is influenced by the presence of near-wall counter-rotating streamwise vortices.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Also, at a fixed time, hot and cold spots alternate in the streaks. Such temperature variations are consistent with near-wall flow and surface visualizations reported in the literature [3][4][5]7] and have been attributed to variations in near-wall fluid temperature that is influenced by the presence of near-wall counter-rotating streamwise vortices.…”
Section: Resultssupporting
confidence: 85%
“…Other studies have, in addition, spatially locked the near-wall vortical structures by the use of flutes at the exit of the slot nozzle Table 1 Distribution of the temperature fluctuations among the dominant modes during slot jet impingement, scaled with the total fluctuations in the filtered dataset [19]. In a closely related study of cross-flow over a cylinder [3], an array of equally spaced wires upstream of the flow were used to lock the structures spatially. In the present study, the jet is not perturbed either temporally or spatially; hence, slight imperfections in the nozzle geometry or nozzle-to-surface spacing could cause the temporally oscillating thermal structures to be displaced/skewed spatially.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanfossen & Simoneau (1987) used wires to create vortices perpendicular to a downstream cylinder and studied the resulting fluid flow and heat transfer near the surface using a combination of smoke visualization and liquid crystals. It was observed that regions where vortices forced fluid towards the surface corresponded to regions of increased heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The former spacing corresponds to a large gradient in spatial temperature distribution along the x coordinate, while the latter corresponds to an unstable reattachment. Near-wall flow structure and/or the impingement surface temperature have been documented in several studies for jet impingement (VanFossen and Simoneau, 1987;Yokobori et al, 1988;Kataoka et al, 1994). Sakakibara et al (1997) measured, simultaneously, the near-wall vortex structure and fluid temperature distribution in the impingement region.…”
Section: Regular Papermentioning
confidence: 99%